2007
DOI: 10.1080/02701367.2007.10599431
|View full text |Cite
|
Sign up to set email alerts
|

Career Evolution and Knowledge of Elite Coaches of Swimmers With a Physical Disability

Abstract: In the last decade there has been an increase in empirical research on coaches of elite able-bodied athletes, while coaches of athletes with a disability have generally been overlooked. Thus, the purpose of the current study was to address this oversight by examining the career evolution and knowledge of these coaches. Six elite coaches of swimmers with a physical disability were interviewed using an unstructured, open-ended interview format. Results revealed information pertaining to the coaches' backgrounds,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0
26

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(134 citation statements)
references
References 17 publications
6
102
0
26
Order By: Relevance
“…Cregan, Bloom & Reid, 2007;Nash and Sproule, 2009;Schinke, Bloom & Salmela, 1995) has acknowledged coaches' careers, the focus has been on the development of 'expertise' rather than questioning the context in which these 'experts' operate. As such, focusing on individual coaches' understandings of their career pathways and their lived experiences (Van Manen, 1990) might not only provide us with potentially rich insights into contemporary working contexts in which coaches operate, but also the ways in which they may construct their respective coaching identities, inclusive of the emotions (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cregan, Bloom & Reid, 2007;Nash and Sproule, 2009;Schinke, Bloom & Salmela, 1995) has acknowledged coaches' careers, the focus has been on the development of 'expertise' rather than questioning the context in which these 'experts' operate. As such, focusing on individual coaches' understandings of their career pathways and their lived experiences (Van Manen, 1990) might not only provide us with potentially rich insights into contemporary working contexts in which coaches operate, but also the ways in which they may construct their respective coaching identities, inclusive of the emotions (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Equally we sought to understand Maeve's experience using existing literature (e.g. Cregan, Bloom & Reid, 2007;Nash and Sproule, 2009;Schinke, Bloom & Salmela, 1995;) that have investigated coaches' career trajectories. Similar to the work of Nelson et al (2013), this proved to be a much messier process than is often depicted in the literature, as we at times disagreed on the utility or deployment of particular sense-making concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research reports that coaches' approaches to working with athletes of different skill levels are varied and dependent on what coaches believe is needed to create an optimal learning environment for their athletes (Cregan, Bloom, & Reid, 2007). To pursue these lines of future research, the need for longitudinal data among diverse samples of coaches is underscored.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…More specifically, playing experience (Cregan et al, 2007;Hardin, 2000;Salmela, 1994), coaching and interacting with other coaches (Gould et al, 1990;Fleurance & Cotteaux, 1999;Schinke et al, 1995), and mentoring (Bloom, Durand-Bush, Schinke, & Salmela, 1998), have been identified as sources coaches use to develop coaching knowledge and sport-specifie knowledge.…”
Section: Learning To Coach Through Experiencementioning
confidence: 99%
“…More specifically, the acquisition of coaching knowledge through competitive sport experiences (Cregan, Bloom, & Reid, 2007;Hardin, 2000;Salmela, 1994;Schinke, Bloom, & Salmela, 1995), interactions with other coaches (Gilbert & Trudel, 2001;Gould et al, 1990) and mentoring (Bloom, Durand-Bush, Schinke, & Salmela, 1998) have been identified as sources coaches used to develop coaching knowledge and sport-specifie knowledge. Although valuable to the study of coach development, it is important to note that all of the aforementioned studies were based on elite-level coaches, most commonly at the university or Olympie levels.…”
Section: Resumémentioning
confidence: 99%